2014
DOI: 10.2514/1.b35128
|View full text |Cite
|
Sign up to set email alerts
|

Multifidelity Multidisciplinary Whole-Engine Thermomechanical Design Optimization

Abstract: Traditionally the optimization of a turbomachinery engine casing for tip clearance has involved either 2D transient thermo-mechanical simulations or 3D mechanical simulations. The following paper illustrates that 3D transient whole engine thermomechanical simulations can be used within tip clearance optimizations and that the eciency of such optimizations can be improved when a multi-delity surrogate modeling approach is employed. These simulations are employed in conjunction with a rotor sub-optimization util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The literature contains a number of examples of the effectiveness of this technique on problems including airfoil design [23][24][25], the creation of aerodynamic models [25][26][27][28][29], compressor blade design [3] and even whole engine optimization [10].…”
Section: Krigingmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature contains a number of examples of the effectiveness of this technique on problems including airfoil design [23][24][25], the creation of aerodynamic models [25][26][27][28][29], compressor blade design [3] and even whole engine optimization [10].…”
Section: Krigingmentioning
confidence: 99%
“…The manual effort required in such design studies can be considerably reduced by employing modern design automation and optimization techniques and there are, of course, numerous examples of such techniques being applied throughout the literature. Aerofoil sections [1,2], compressor blades [3], wings [4], aircraft [5], combustors [6][7][8] and whole engines [9,10], for example, have all been the subject of automated design optimizations in recent years. However, the majority of engineering design optimization examples within the literature include a fundamental limitation which can limit the benefits that such automation can bring to real world problems.…”
Section: Introductionmentioning
confidence: 99%
“…Due to advances in computational power and simulation efficiency, whole engine models (WEMs) have become a staple tool in the design process of gas turbine engines in industry (Voutchkov et al 2006;Arkhipov et al 2009;Toal et al 2014). Analyzing WEMs allows engineers to capture both the physics of inter-component interactions and also emergent behaviour that would otherwise be lost if the analysis was done on each component in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…In the current work, Kriging and its auto-regressive multi-fidelity variant, Co-Kriging (Kennedy and O'Hagan 2000), are used, as the formulation provides estimates of the prediction error which can be subsequently used to search for infill points. Toal et al (2014) demonstrated the use of Co-Kriging models for reducing the frequency of performing expensive whole engine transient thermo-mechanical simulations in the optimization of a high-pressure compressor for minimum specific fuel consumption. The thermal results were supplemented with a larger number of relatively cheap steady-state mechanical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…A 3D finite element mesh typically contains several million degrees-offreedom (DOF) and one single simulation may take hours or perhaps days to complete [1]. Previous whole engine optimisations, such as those of Toal et al [2], for example, employed whole engine transient thermo-mechanical simulations taking several days to evaluate even on a high performance compute cluster and resulted in design optimisations taking months to perform. Due to this time restriction the number of variables included in a design optimisation tends to be very small which may potentially lead to a suboptimal design.…”
Section: Introductionmentioning
confidence: 99%